The Effects of Vegetarian and Vegan Diets on Gut Microbiota - Tomova, Aleksandra; Bukovsky, Igor; Rembert, Emilie; Yonas, Willy; Alwarith, Jihad; Barnard, Neal D.; Kahleova, Hana (Frontiers in Nutrition, 2019)
The difference in gut microbiota composition between individuals following vegan or vegetarian diets and those following omnivorous diets is well documented. A plant-based diet appears to be beneficial for human health by promoting the development of more diverse and stable microbial systems. Additionally, vegans and vegetarians have significantly higher counts of certain Bacteroidetes-related operational taxonomic units compared to omnivores. Fibers (that is, non-digestible carbohydrates, found exclusively in plants) most consistently increase lactic acid bacteria, such as Ruminococcus, E. rectale, and Roseburia, and reduce Clostridium and Enterococcus species. Polyphenols, also abundant in plant foods, increase Bifidobacterium and Lactobacillus, which provide anti-pathogenic and anti-inflammatory effects and cardiovascular protection. High fiber intake also encourages the growth of species that ferment fiber into metabolites as short-chain fatty acids (SCFAs), including acetate, propionate, and butyrate. The positive health effects of SCFAs are myriad, including improved immunity against pathogens, blood–brain barrier integrity, provision of energy substrates, and regulation of critical functions of the intestine. In conclusion, the available literature suggests that a vegetarian/vegan diet is effective in promoting a diverse ecosystem of beneficial bacteria to support both human gut microbiome and overall health. This review will focus on effects of different diets and nutrient contents, particularly plant-based diets, on the gut microbiota composition and production of microbial metabolites affecting the host health.